Physicochemical properties of Walnuts (Juglans regia L.) shells and kernels growing in different locations in Kurdistan region-Iraq - Salih, Hayman Saeed (Sulaimani Journal for Pure and Applied Sciences, 2020)
Some physicochemical properties of walnut shell, kernel and oil of fifteen samples of walnut grown in different locations in Kurdistan region-Iraq were determined. Three principal dimensions such as length, width and thickness, volume and projected area of walnut and its kernels were measured using image processing technique. Based on three principal dimensions, some dimensional properties including geometric mean diameter, arithmetic mean diameter, sphericity, volume and surface area of the nuts and kernels were calculated. Also gravimetric properties of nuts and kernels such as true density of nuts and kernels were studied. Furthermore other physical properties such as weight of nut, weight of kernel, percentage yield of walnut, total oil content, ash contents, moisture contents, pH value, relative density and refractive index of the oils were also determined. The variations in physical properties such as size dimensions, arithmetic mean diameter, geometric mean diameter, unit mass, sphericity, surface area, true density and volume of shells and kernel of walnuts as a function of the moisture content were determined. With an increase in the moisture content, the surface area, sphericity, true density and volume of shells and kernel of walnuts increased. In addition, the oil yields from the kernels had ranged between 36.07% to 70.24%. The moisture contents of shells and kernels ranged between 6.34% to 10.11% and 3.68% to 5.62%, respectively; and the ash content of kernels were ranged between 0.94% to 2.2%. On the other hand, the refractive index of oils were determined between 1.4734 and 1.4767, pH-values of kernel oils were ranged between 6.23 and 7.02 and the relative density were determined between 0.9746 and 0.9801. Finally the present study was showed that the walnut kernels in Kurdistan region did not show any considerable significant variations with reference to their physical and chemical properties.
Keywords: walnut (Juglans regia L.); physicochemical properties; moisture content; refractive index